Ontologia e corpo-mente in psicoanalisi: Una nota sulla psicanalisi ontologica di Thomas H. Ogden - Lombardi, Riccardo (B@belonline, 2021)
The author explores the link between ontological psychoanalysis and a psychoanalytic vertex focused on the Body-Mind relationship. Thomas H. Ogden recently recognized the importance of Winnicott’s and Bion’s intuitions on the importance of Being. This focus is an evolution of the more classical view centered on relational conflicts and is consistent with contemporary patients’ most essential needs. In this paper the author explores points of agreements and differentiations with Ogden’s proposals.